Kaolinization of Tertiary Volcanic Rocks in the Biga Peninsula (Lapseki-╟anakkale), Turkey - Lacin, Davut (Asian Journal of Chemistry, 2010)
This study presents preliminary results on the kaolinization of tertiary magmatic units in the Biga Peninsula. Volcanic and intrusive rocks of tertiary age crop out in the vicinity of the Harmancik and Üçpinar villages of Çanakkale country, Lapseki town. Volcanic rocks consist of andesites, basalts and rhyolites, whereas intrusive rocks consist of granitic plutons. The granitic intrusions cut the volcanic rocks. Kaolin deposits appears to form within the andesitic rocks. The kaoline deposit is located at nearly 3 km northeast of Üçpinar village. Outcrops of the deposit extends along a north-south trend with a width of 200-250 m and a length of 600-700 m, reaching 10-15 m in thickness. The presence of clays minerals accompanied with feldspars and kaolinite indicates that the solutions from which the clay minerals precipitated were enriched in some alkali and alkali-earth ions. This implies weak kaolinization. Besides, sudden and sharp temperature fluctuation of the solution due to seasonal rainfall seems to have prevented mobile silica movement upwards and resulted high amount of finely dispersed α-quartz (SiO2 > 75 %) within the kaolin deposits. As a result, the dissolved silica did not replace and silicify the main rocks and therefore, a "silica-gossan" did not develop. This can also be considered as an another evidence for weak kaolinization. It is argued that the kaolinization within the study area was formed by hydrothermal fluids circulating through the faults.